MARKETING SYSTEM AND CONSUMER PREFERENCES TOWARDS SWEET AND SALTY TASTE POTATO IN DISTRICT MULTAN - Iqbal, M. A.; Qasim, M. A.; Aslam, M.; Yasin, M.; Imran, M. A. (Pak. J. Agri. Engg., Vet. Sci., 2024)
In several agro-climatic regions, including Pakistan, potato is a significant crop that is farmed extensively. Potato production and home consumption are important in Pakistan. It is one of the four main staple foods that greatly contribute to domestic food consumption and demands in the country. Due, to several production and marketing restrictions, the performance of the potato business remains below optimal levels despite increases in area and production. One of them is a lack of understanding of consumer preferences study in hand evaluated consumer preferences for sweet taste and salty taste potatoes by gathered information from various areas of the district Multan through a survey of 75 potato consumers, 75 farmers, 15 wholesalers, 15 commission agent, and 15 retailers from various social classes. By using Stata 13.1, descriptive statistic and Binary Logit methods were applied to analyse the data. Consumers' preferences for buying and eating potatoes varied. Different factors, such as taste, freshness, aesthetics, income, age, education, and price paid for potato, had an impact on their consumer preferences. These results may assist in bridging Pakistan's policymakers, and consumers' differing perceptions of quality. To increase their profitability and the satisfaction of potato consumers in Pakistan, supply chain participants should respond to quality attributes consumers consider important in their purchase preferences. Both public and private sectors should involve to arrange trainings and outreach activities for the farming community in this regard.